Multi-omics landscape of alternative splicing in diffuse midline glioma reveals immune- and neural-driven subtypes with implications for spliceosome-targeted therapy - Liu, Chaxian; Liu, Yue; Lin, Hao; Zhang, Chufan; Zhang, Bilong; Song, Haikun; Fan, Xiaomin; Lyu, Yi; Yang, Hui; Mao, Ying (Frontiers in Immunology, 2025)
IntroductionH3K27-altered diffuse midline glioma (DMG) is a highly aggressive glioma subtype, accounting for approximately 60% of pediatric high-grade gliomas, with a median survival of less than 12 months. Due to its predominant localization in the brainstem, conventional surgical resection is often unfeasible, underscoring the urgent need for alternative therapeutic strategies. While previous studies on DMG have primarily focused on regulatory mechanisms at the protein level, the role of alternative splicing in DMG remains largely unexplored. Given its potential impact on gene regulation and tumor progression, a comprehensive analysis of alternative splicing could provide novel insights into targeted or immune therapeutic strategies, complementing existing transcriptomic studies of DMG.MethodsTo investigate the alternative splicing landscape of DMG, we performed transcriptome sequencing (RNA-seq) on patient-derived H3WT and H3K27-altered DMG cell lines, integrating these data with RNA-seq and single-cell transcriptomic (scRNA-seq) datasets from published sources. This comprehensive approach enabled us to delineate the alternative splicing landscape of H3K27-altered DMG and validate its distinct features at the cellular level.ResultsOur multi-omics analysis revealed significant transcriptional alterations in H3K27-altered DMG compared to H3WT DMG, particularly in pathways related to neuro-regulation, metabolism, and immunity. Further in-depth analysis identified extensive alternative splicing changes in H3K27-altered DMG, predominantly associated with RNA modifications and key alterations in extracellular matrix and nucleotide metabolism. Integrating these findings, we characterized five RNA-associated proteins that enabled a binary classification of DMG into neural and immune subtypes, with each subtype exhibiting distinct prognostic and transcriptomic features. Notably, we identified RALYL as a potential key regulator in DMG progression.DiscussionOur findings indicate that H3K27-altered DMG exhibits significant alternative splicing alterations, which play crucial roles in tumorigenesis and progression. Additionally, our study identified an RNA-binding protein-based classification of DMG and characterized RALYL as a potential regulatory factor, highlighting its potential as a novel therapeutic target.